Cancer cells increase endothelial cell tube formation and survival by activating the PI3K/Akt signalling pathway. Issue 1 (December 2017) - Cheng, Hao-Wei; Chen, Yi-Fang; Wong, Jau-Min; Weng, Chia-Wei; Chen, Hsuan-Yu; Yu, Sung-Liang; Chen, Huei-Wen; Yuan, Ang; Chen, Jeremy
Abstract Background Angiogenesis is a hallmark of cancer and plays a critical role in lung cancer progression, which involves interactions between cancer cells, endothelial cells and the surrounding microenvironment. However, the gene expression profiles and the changes in the biological phenotype of vascular endothelial cells after interactions with lung cancer cells remain unclear. Methods An indirect transwell co-culture system was used to survey the interaction between human umbilical vein endothelial cells (HUVECs) and human lung adenocarcinoma CL1-5 cells, as well as to investigate the morphological and molecular changes of HUVECs. The differentially expressed genes (DEGs) in HUVECs after co-culture with cancer cells were identified by microarray. Moreover, a publicly available microarray dataset of 293 non-small-cell lung cancer (NSCLC) patients was employed to evaluate the prognostic power of the gene signatures derived from HUVECs. Results The interaction between HUVECs and lung cancer cells changes the morphology of HUVECs, causing them to have a mesenchymal-like morphology and alter their cytoskeleton organization. Furthermore, after co-culture with lung cancer cells, HUVECs showed increased cell motility and microvessel tube formation ability and a decreased apoptotic percentage. Transcriptomic profiling of HUVECs revealed that many survival-, apoptosis- and angiogenesis-related genes were differentially expressed after interactions with lung cancer cells. Further investigations showed that the PI3K/Akt signalling pathway and COX-2 are involved in endothelial tube formation under the stimulation of lung cancer cells. Moreover, Rac-1 activation might promote endothelial cell motility through the increased formation of lamellipodia and filopodia. The inhibitors of PI3K and COX-2 could reverse the increased tube formation and induce the apoptosis of HUVECs. In addition, the gene signatures derived from the DEGs in HUVECs could predict overall survival and disease-free survival in NSCLC patients and serve as an independent prognostic factor. Conclusions In this study, we found that cancer cells can promote endothelial cell tube formation and survival, at least in part, through the PI3K/Akt signalling pathway and thus change the microenvironment to benefit tumour growth. The gene signatures from HUVECs are associated with the clinical outcome of NSCLC patients.